DESCOLAMENTO DE RETINA REGMATOGÊNICO PÓS-TRAUMA, EM CÃO: RELATO DE CASO - Dal Chiavon, Gessica; da Silva, Adriane Siqueira; Simão, Iago; Guerra, Jéssyca; Wurfel, Simone de Fátima Rauber; Massa, Isadora Morais; Lusa, Tatiane (Anais de Medicina Veterinária, 2022)
.